Correlation between compression index and basic soil parameters for cohesive soil in Samarahan, Sarawak - Lee, Yee Yong, 1987-, author; Khairul Anuar Kassim, supervisor; Fakulti Kejuruteraan Awam (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2011